Combined unstable damage to the pelvis and abdominal organs. Justification of treatment tactics - O.A. Burianov; V.Р. Kvasha; V.M. Diomin; V.M. Lianskorunskyi; D.V. Miasnikov (Медицина неотложных состояний)
Background. Combined injuries of the pelvis and abdominal organs are common in multiple trauma patients, due to anatomical proximity. According to various authors, they account from 4 to 23 % of cases. The epidemiology of abdominal organ injuries combined with pelvic fractures includes the liver, kidneys, and spleen in 36.6 % of cases; isolated vascular injuries (mesentery/iliac/thoracic aorta) in 15.1 %; hollow organs (bladder, intestine) in 14.0 %; hollow organs + vascular injuries in 10.8 %; parenchymal organs + vascular injuries in 9.7 %; parenchymal organs + hollow organs in 6.5 %; and parenchymal organs + diaphragm in 6.5 %. The mortality rate for pelvic fractures and abdominal trauma is approximately 5–10 %, which is attributed to hemodynamic instability in this cohort. The purpose was to improve treatment outcomes in patients with combined pelvic and abdominal organ injuries by optimizing treatment strategy. Materials and methods. The clinical study included 34 patients with combined pelvic and abdominal injuries, divided into two groups. The experimental group consisted of 21 patients, with a male-to-female ratio of 13 (61.9 %) to 8 (38.1 %). The average age was 44.3 ± 13.3 years. The comparison group included 13 patients, 8 males (61.5 %) and 5 females (38.5 %), with an average age of 43.7 ± 12.9 years. Results. In the experimental group, 6 months post-injury, excellent and good functional outcomes were noted in 7 patients (77.8 %) versus 2 patients (50.0 %) in the comparison group. Unsatisfactory outcomes were observed in 1 case (11.1 %) in the experimental group and 1 case (25.0 %) in the comparison group (p < 0.05). At 18 months post-injury, excellent and good functional outcomes in the experimental group were observed in 6 patients (66.6 %) versus 2 patients (50.0 %) in the comparison group. Unsatisfactory outcomes were noted in 1 case (11.1 %) in the experimental group and 1 case (25.0 %) in the comparison group (p < 0.05). Conclusions. The developed and implemented diagnostic and treatment algorithm, including a novel opposite compression screw design for stabilizing sacroiliac joint injuries, and an active approach to conversion of pelvic stabilization method in patients with combined unstable pelvic and abdominal organ injuries, resulted in excellent and good functional outcomes in 66.6 % of patients. FAST protocol, diagnostic peritoneal lavage, abdominal and pelvic computed tomography scans help objectify clinical data. Each method has its advantages, limitations, and specific indications for use.